How many days are needed for a reliable assessment by the Sleep Diary? - Diego de Alcantara Borba; Raquel Sousa Reis; Pedro Henrique Tadeu de Melo Lima; Lucas Alves Facundo; Fernanda Veruska Narciso; Andressa Silva; Marco Túlio de Mello (Sleep Science, 2020)
Introduction: Population sleep registration is important for the epidemiological investigation of possible disorders and diseases associated with sleep deprivation and restriction. The aim of the current study was to verify how many days and weeks are required for a reliable sleep diary application. Methods: 53 subjects of both genders participated in the study (Age: 25±9 years). The volunteers answered the morning-evening questionnaire for later identification of their chronotype (21 mornings; 22 undetermined; 10 evenings). They then received the sleep diary to fill in for a period of 28 consecutive days (or 4 weeks) of their nighttime sleep. The participant was instructed to describe the time at which they started sleeping and woke up within one hour after waking up. Results: There was no difference in participants’ sleep time between weeks. The participants had longer sleep times on Sunday and Saturday compared to other days of the week. The sleep diary reliability values increased with the increasing number of nights, reaching adequate reliability (≥ 0.70) with seven consecutive days recorded. Conclusion: A sleep diary seems to be a reliable tool for assessing adult sleep time, especially when used for a period of at least seven consecutive days including weekends.